THE ANALYSIS OF SEXUAL CONSENT RULES IN ARTICLE 5 OF PERMENDIKBUD RISTEK NUMBER 30 OF 2021 REVIEWED FROM THE PERSPECTIVE OF ISLAMIC LAW - Surjanti Surjanti; Yudi Setiyono; Widowati Widowati; Retno Sari Dewi; David Budi Laksono (International Journal of Artificial Intelligence Research, 2022)
Regarding the treatment of sexual violence (PPKS) in tertiary institutions, the government released PERMENDIKBUD RISTEK No. 30 of 2021. However, that does not imply that this ministerial regulation is without flaws or shortcomings. The phrase "Without the assent of the victim" in article 5 seems to legitimize adultery and LGBT behavior based on consent, which is one of the reasons this ministerial decree generates inconsistencies. Therefore, this study was done to examine sexual consent and determine the effects of adultery according to Shafi'i belief system on Islamic lawAccording to the law, it is acceptable to use the phrase without the victim's agreement under article 5 paragraph 2 of Minister of Education, Culture, Research, and Technology Number 30 of 2021. Without the victim's agreement will cause a difficulty and a debate in society if it is interpreted as an Argumentum a contrario. Because it is possible to read the phrase "without the victim's consent" to mean that if both parties agree to engage in sexual activity, there is no issue and the behavior is appropriately referred to as "sexual consent". Therefore, it appears that in this instance, Minister of Education, Culture, Research, and Technology Number 30 has consented to the legalization of adultery in tertiary institutions. According to Islamic law, adultery and extramarital sex are forbidden acts because they violate Allah's command in Surah Al-verse Isra's 32. The existence of pregnant marriages is one of the effects of adultery.